(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the history of the reward system in Uzbekistan in the 20th century is reflected on the example of Fergana region. In particular, on the basis of the documents of the State Archive of the Fergana region, the process of gradual awarding of each profession in the region is reflected. Also, in the years after the Second World War, a comparative analysis of the awarding of the inhabitants of the valley with awards established as an anniversary, orders and medals of varying degrees was carried out.